Accumulation of plasma levels of anthocyanins following multiple saskatoon berry supplements. (2nd April 2020) - Fang, Jim; Huang, Jiannan
Abstract: 1. Anthocyanins are a subgroup of flavonoids responsible for the blue, purple and red color of many fruits, flowers and leaves. Consumption of foods rich in anthocyanins is associated with a reduced risk of cardiovascular disease and cancer. Most food intervention studies employ once or twice per day dose schedules. 2. The current study demonstrated that plasma concentrations of cyanidin-3-galactoside and cyanidin-3-xyloside, the two major components of saskatoon berries, were significantly increased following three consecutive saskatoon berry supplements 4 hours apart. This accumulation is due to the residual concentrations of anthocyanins at the time of second and third supplements. 3. Accumulation was especially pronounced for peonidin-3-glucoside and peonidin-3-galactoside, the methylated metabolites of cyanidin-3-glucoside and cyanidin-3-galactoside, respectively. Little or no accumulation was observed for cyanidin-3-arabinoside and cyanidin-3-glucoside, two other components of saskatoon berries, possibly due to their short half-lives. 4. Thus, taking anthocyanin supplements with every meal would provide higher plasma concentrations for some anthocyanins and their metabolites than the once or twice-a-day dose regimens.